2008
DOI: 10.1108/14637150810876698
|View full text |Cite
|
Sign up to set email alerts
|

Design for supply chain collaboration

Abstract: Purpose -The purpose of this paper is to clarify the architecture of supply chain collaboration and to propose a design for supply chain collaboration (DfC), which enables participating members to create and develop key elements of the proposed architecture. Design/methodology/approach -The paper offers a concept for designing the five elements of the architecture of supply chain collaboration, namely collaborative performance system, decision synchronisation, information sharing, incentive alignment, and inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
149
0
13

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(178 citation statements)
references
References 18 publications
3
149
0
13
Order By: Relevance
“…Prior research has suggested that both BPM and SCC are important for improving performance and competitiveness (e.g., Simatupang and Sridharan, 2008;Zacharia et al, 2009;Nyaga et al, 2010); however, it lacks empirical testing of their relationship. The identification of such a link based on empirical evidence can provide a better understanding of how intra-organisational development, regarding BPM practice, can help with collaborative activities, and of the benefits that can, thereby, be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has suggested that both BPM and SCC are important for improving performance and competitiveness (e.g., Simatupang and Sridharan, 2008;Zacharia et al, 2009;Nyaga et al, 2010); however, it lacks empirical testing of their relationship. The identification of such a link based on empirical evidence can provide a better understanding of how intra-organisational development, regarding BPM practice, can help with collaborative activities, and of the benefits that can, thereby, be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…A colaboração entre os participantes da cadeia de suprimentos pode ser a chave para a melhoria de processos nas organizações (Green et al, 2006) e pode ser definida como um processo em que empresas independentes trabalham em conjunto com o objetivo de entregar produtos aos consumidores finais, buscando otimizar os resultados para os membros da cadeia e criando vantagem competitiva (Simatupang & Sridharan, 2008).…”
Section: Colaboraçãounclassified
“…Decision synchronisation and incentive alignment as two of the architectural elements of supply chain collaboration are essential for effective system-level disruption responses (Simatupang and Sridharan, 2008). Pettit et al (2010) suggested that a global supply chain must create strong capabilities in the fields of collaboration, visibility and flexibility in order to effectively manage their huge number of interconnected operations between several tiers of suppliers and customers, consequently contributing to balanced resilience.…”
Section: Supply Chain Resilience Frameworkmentioning
confidence: 99%